PENGARUH LAYANAN INFORMASI TERHADAP PENINGKATAN MINAT SISWA TENTANG PERGURUAN TINGGI KELAS XI FARMASI IKASARI PEKANBARU T.P. 2014/2015 - Umari, Tri Umari; ', Mulyono; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The title of this research is "Effect On The Improvement Of Information Services Student Interest On Higher Education Class XI Farmasi Ikasari Pekanbaru T.P. 2014/2015”. The aim in this study were 1) To know the description given level of student interest before the service information, 2). To know the process of implementation of information services on the college, 3). To describe the level of interest of the students after being given information services, 4). To determine differences in the level of interest of the students before and after the information services, 5). To find out How much influence information services to increase student interest. The subjects were students of class XI Farmasi IKASARI pekanbaru totaling 116 students. This study uses a total of sampling (samples saturated). Which means that all members become members of the sample population. Picture of student interest before being given the information service of 75% in the high category, the category was 24.14% and 0.86% lower categories. Picture of student interest after being given information service 97.41% in the high category, the category of medium and low category 2:59% 0%. Based on the calculation results obtained that the correlation coefficient between  Is equal to 0495, then the determinant coefficient () is   = 0.245 x 100 = 24.5 %. So the contribution of information services by 24.5%, while 75.5% of other factors. Judging from the t test with dk 230 and standard error set at 5%, then t_tabel = 1.980. Which means that in this study there is a significant difference to the increasing interest of the students before and after being given the information services. Key words : Information Services, Higher Education Interests